Acoustic-emission investigation of failure of high strength concrete - J. HOŁA (Archives of Acoustics)
This paper presents results of acoustic-emission investigations of the failure of high-strength concrete. Concretes differing in their composition and compressive strength were tested. Several acoustic emission (AE) parameters were recorded as a function of failure time. It has been shown that the failure of such concretes is signalled, starting from a certain stress level, by visibly intensifying acoustic activity. An analysis of the AE measurements has shown that the failure of the tested high-strength concretes is not continual but multistage. Stress values which delimit these stages have been determined.